“Assessment in Dialogue” (AID). Assessing the Communicative Action - Piasta-Siechowicz, Joanna (Respectus Philologicus, 2018)
“Assessment in Dialogue” (AID) is a model of Joanna Piasta-Siechowicz addressed to the participants of general education: students-teachers-parents. AID reconciles contradictory tendencies of the philosophy and praxis of student assessment: the pursuit of objectivity of the former and the need of individualisation of the latter. It aspires to combine the objectivity of requirements and evaluation criteria with the need of individualisation. It is also well suited to help teachers in systematic planning of their work. “Assessment in Dialogue” refers to the trisubjectivity (student-parent-teacher) in the planning and organisation of student’s activities and, as a result, in informing about his/her achievements during a lesson. Implemented in a primary school since 2012, “Assessment in Dialogue” is popularised at conferences of principals and teachers in Poland and Ireland, workshops for teachers, publications in methodical journals. It is grounded in the official documents of the Ministry of National Education, European Council recommendations and conclusions from ten years of constant evaluation of the psycho-didactic process in schools as well as the functioning of evaluation system in Poland.